SOME ECOLOGICAL STUDIES ON OREOCHROMIS ESCULENTUS GRAHAM (PISCES: CICHLIDAE) IN TWO SMALL TROPICAL LAKES - Chale, F M M (Indian Journal of Fisheries, 2011)
Babati and Basotu are two small lakes in northern Tanzania. The former lies in the rift valley and hasinflows and an outflow, while the latter is a closed basin volcanic lake. In Lake Babati, which is surroundedby extensive emergent aquatic macrophytes, both nitrates and orthophosphates were not detected, thephytoplankton populations were sparse and the fish were stunted. In Lake Basotu, both nitrates andphosphates were high and algal densities were also high. Diatoms were plentiful and O.esculentus grewto large size. It was further observed that in this lake, the high salinity affected the maximum fish size.